Design and Operational Elements of the Robotic Subsystem for the e.deorbit Debris Removal Mission - Jaekel, Steffen; Lampariello, Roberto; Rackl, Wolfgang; De Stefano, Marco; Oumer, Nassir; Giordano, Alessandro M.; Porges, Oliver; Pietras, Markus; Brunner, Bernhard; Ratti, John; Muehlbauer, Quirin; Thiel, Markus; et al. (Frontiers in Robotics and AI, 2018)
This paper presents a robotic capture concept that was developed as part of the e.deorbit study by ESA. The defective and tumbling satellite ENVISAT was chosen as a potential target to be captured, stabilized, and subsequently de-orbited in a controlled manner. A robotic capture concept was developed that is based on a chaser satellite equipped with a seven degrees-of-freedom dexterous robotic manipulator, holding a dedicated linear two-bracket gripper. The satellite is also equipped with a clamping mechanism for achieving a stiff fixation with the grasped target, following their combined satellite-stack de-tumbling and prior to the execution of the de-orbit maneuver. Driving elements of the robotic design, operations and control are described and analyzed. These include pre and post-capture operations, the task-specific kinematics of the manipulator, the intrinsic mechanical arm flexibility and its effect on the arm’s positioning accuracy, visual tracking, as well as the interaction between the manipulator controller and that of the chaser satellite. The kinematics analysis yielded robust reachability of the grasp point. The effects of intrinsic arm flexibility turned out to be noticeable but also effectively scalable through robot joint speed adaption throughout the maneuvers. During most of the critical robot arm operations, the internal robot joint torques are shown to be within the design limits. These limits are only reached for a limiting scenario of tumbling motion of ENVISAT, consisting of an initial pure spin of 5 deg/s about its unstable intermediate axis of inertia. The computer vision performance was found to be satisfactory with respect to positioning accuracy requirements. Further developments are necessary and are being pursued to meet the stringent mission-related robustness requirements. Overall, the analyses conducted in this study showed that the capture and de-orbiting of ENVISAT using the proposed robotic concept is feasible with respect to relevant mission requirements and for most of the operational scenarios considered. Future work aims at developing a combined chaser-robot system controller. This will include a visual servo to minimize the positioning errors during the contact phases of the mission (grasping and clamping). Further validation of the visual tracking in orbital lighting conditions will be pursued.